Burkitt’s Lymphoma Presented as Advanced Ovarian Cancer without Evidence of Lymphadenopathy: CT and MRI Findings - Lucia Manganaro; Silvia Bernardo; Maria Eleonora Sergi; Paolo Sollazzo; Valeria Vinci; Alessandra De Grazia; Anna Clerico; Maria Giovanna Mollace; Matteo Saldari (Case Reports in Radiology)
Burkitt's lymphoma is a rare non-Hodgkin's lymphoma which can occasionally involve the ovary and may cause confusion for the clinician since its presentation might mimic other much more frequent tumors. We present a case of a 23-year-old woman with sporadic Burkitt’s lymphoma presented as advanced ovarian cancer with bilateral ovarian masses, peritoneal carcinomatosis, ascites, and marked elevation of CA-125. Liver involvement and atypical bone lesions, such as the cranial vault and the iliac wing, were also detected without evidence of lymphadenopathy. We describe the MRI and CT findings of simultaneous ovarian and bone lesions, which have never been reported in literature in a patient with Burkitt's lymphoma, before and after one cycle of chemotherapy. In evaluating any ovarian neoplasm in a young woman, Burkitt's lymphoma should be considered as a possibility, particularly if associated with bone lesions. MRI is the most useful tool to characterize the ovarian lesions and suggest the diagnosis before the histopathological results.